Site-specific bone differences and energy status in male competitive runners and road cyclists - Chen, Z.; Sherk, V. D.; Sharma-Ghimire, P.; Bemben, M. G.; Bemben, D. A. (Journal of Clinical Densitometry, 2022)
The interaction between mechanical loading and energy availability on bone health in male endurance athletes merits further investigation. The purpose of this study was to compare bone status in male competitive runners and road cyclists and to investigate the influence of energy availability (EA) on bone mineral density (BMD). 18 competitive runners and 19 road cyclists (20-50 years) participated in this study. Areal BMD and body composition were assessed by dual energy x-ray absorptiometry. Volumetric bone variables at the 4% and 66% tibia sites were assessed by peripheral quantitative computed tomography. Energy availability (EA, 7-day dietary and exercise logs) and resting metabolic rate (RMR, open circuit spirometry) were measured as indicators of energy status. Bone loading history, calcium intake, and training history were assessed by questionnaires. After adjusting for age, runners had significantly greater (p < 0.05) areal BMD (femoral neck, left total hip), Z-scores (total body, hips sites), total bone mineral content and trabecular variables (bone mineral content, volumetric BMD, bone strength index) at tibia 4% site, and total volumetric BMD at tibia 66% site than the cyclists (p = 0.05). At the tibia 66% site, cyclists had significantly greater (p < 0.05) total area, periosteal circumference, endosteal circumference, and strength-strain index than runners. Energy variables were similar for runners and cyclists; however, RMR and RMR ratio (measured RMR/predicted RMR) were significantly lower in cyclists (p < 0.001). In conclusion, there were site-specific differences in hip and tibia bone characteristics between runners and cyclists. RMR was associated with several bone outcomes; however, EA was not related to bone health in runners or to dual energy x-ray absorptiometry bone variables in cyclists.